Pengaruh Modul Hipertensi Berbasis Model IMB (Information, Motivation, end Behavioral Skill) dalam Meningkatkan Kepatuhan Minum Obat Pada Pasien Hipertensi - Nelyta Oktavianisya; Sugesti Aliftitah (PrimA: Jurnal Ilmiah Ilmu Kesehatan, 2025)
Hypertension remains the most common chronic disease found in primary healthcare facilities. Many patients return with recurring complaints due to uncontrolled blood pressure, one of the main causes being non-compliance with medication. Patient compliance can be defined as a patient's adherence to prescribed therapy. Medication adherence and adherence to treatment are crucial for a speedy recovery. Blood pressure control and adherence to antihypertensive treatment are crucial for preventing complications. The purpose of this study was to determine the effect of the Hypertension Module Based on the IMB Model in Improving Medication Adherence in Hypertensive Patients. The design used was a one-group pre-post test design. The population in this study was 68 people, and using simple random sampling techniques, 36 people were obtained. The results showed that the average medication adherence before the intervention was 5.61 with a standart deviation of 0.766. The average medication adherence after the intervention increased to 5.89 with a standart deviation of 0.919. The Wilcoxon test for medication adherence data showed a ρ value of 0.006 with an α of 0.05. Since ρ value <α, the IMB-based hypertension module is effective in improving medication adherence in hypertensive patients. With adequate knowledge, a person will strive to adhere to treatment, seek further understanding of the disease, and utilize experience to motivate them to adhere to treatment and change behavior